Odpowiedź :
Odpowiedź:
a) 4x - 3x = 5 + 3
x = 8
b) 5x + 3x = 7 - 2
8x = 5 | : 8
x = 5/8
c) 3x - 3 = 0
3x = 0 + 3
3x = 3 | :3
x = 1
d) -6x - 6 = 24
-6x = 24 + 6
-6x = 30 | : (-6)
x = -5
e) -7x + 14 = 3x - 1
-7x - 3x = -1 - 14
-10x = -15 | : (-10)
x = 1,5
f) 4x - 4 = 6 + 6x
4x - 6x = 6 + 4
-2x = 10 | : (-2)
x = -5
przepraszam z góry za jakieś błędy
a) 4x-3=3x+5
4x-3x=3+5
x=8
b) 5x+2=7-3x
5x+3x=-2+7
8x=5 |:8
x=0,625
c)3(x-1)=0
3x-3=0
3x=-3+0
3x=-3 |:3
x=-1
d)-6(x+1)=24
-6x-1=24
-6x=1+24
-6x=25 |:6
-x=4 1/6
e) -7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-14-1
-10x=-15 |:10
-x=-1,5
f)4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=4+6
-2x=10 |:2
-x=5
liczę na naj :)
4x-3x=3+5
x=8
b) 5x+2=7-3x
5x+3x=-2+7
8x=5 |:8
x=0,625
c)3(x-1)=0
3x-3=0
3x=-3+0
3x=-3 |:3
x=-1
d)-6(x+1)=24
-6x-1=24
-6x=1+24
-6x=25 |:6
-x=4 1/6
e) -7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-14-1
-10x=-15 |:10
-x=-1,5
f)4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=4+6
-2x=10 |:2
-x=5
liczę na naj :)